1996
DOI: 10.1042/bj3140305
|View full text |Cite
|
Sign up to set email alerts
|

Signalling mechanisms of endothelin-induced mitogenesis and melanogenesis in human melanocytes

Abstract: To understand the signalling mechanisms involved in the dual stimulatory effects of endothelin-1 (ET-1) on DNA synthesis and melanization in cultured human melanocytes, we analysed the biological profile of ET-1 receptor and determined the effects of ET-1 on the protein kinase C, cyclic AMP system and mitogen-activated protein kinase (MAP kinase) in comparison with their relevant stimulants. The photoaffinity labelling of ET-1 receptors with Denny-Jaff reagents revealed an ET-1 receptor with a molecular mass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(171 citation statements)
references
References 45 publications
6
163
0
1
Order By: Relevance
“…DAG has been reported to activate MAPK via protein kinase C. The action of ET-1 is transmitted to stimulate cell proliferation mainly via MAPK. 9,20) The present study showed that the extract of A. officinalis did not affect the intracellular signal transduction pathway located upstream of calcium mobilization, i.e., the binding of ET-1 to the ET B R on NHMC or the production of IP 3 . In contrast, the ET-1-induced activation of MAPK was inhibited by the extract.…”
Section: Discussionmentioning
confidence: 86%
“…DAG has been reported to activate MAPK via protein kinase C. The action of ET-1 is transmitted to stimulate cell proliferation mainly via MAPK. 9,20) The present study showed that the extract of A. officinalis did not affect the intracellular signal transduction pathway located upstream of calcium mobilization, i.e., the binding of ET-1 to the ET B R on NHMC or the production of IP 3 . In contrast, the ET-1-induced activation of MAPK was inhibited by the extract.…”
Section: Discussionmentioning
confidence: 86%
“…This is in sharp contrast to Kit-null mutant mouse, which displays severe loss of melanocytes (Cable et al, 1995;Mayer, 1979;Russell, 1979). Interestingly, engineered Kit-null neural crest cultures can sustain melanoblast survival (Hou et al, 2000) through activation of the endothelin pathway that converges with the MAPK pathway like that of Kit (Imokawa et al, 1996). Furthermore, heterozygosity of the tumor-suppressor neurofibrinogen-1, a known negative regulator of RAS-MAPK pathway, gives a partial rescue of Kit-mutations in the mouse (Ingram et al, 2001).…”
Section: Mitf Guards Survival Of Melanocytes and Melanoma Cellsmentioning
confidence: 99%
“…ET-3 and its receptor, Ednrb, are required for normal differentiation and development of melanocytes and Auerbach plexus cells, the enteric ganglia of the gut (for a review see McCallion and Chakravarti, 2001). Ednrb is a G-protein-coupled receptor of the seven-transmembrane family that is thought to modulate cAMP levels (Fuchs et al, 2001) and activate the RAS-MAP-kinase pathway (Imokawa et al, 1996). The temporal need for Ednrb in melanocyte and enteric ganglia has been elegantly examined using engineered mice (Shin et al, 1999) in which inducible expression of Ednrb identified a critical period between embryonic days 10 and 12.5 for the development of these two lineages.…”
Section: Mitf-m Is Critical For the Melanocyte Fate In The Neural Crementioning
confidence: 99%
“…Melanocyte dendrite formation is regulated through multiple signaling pathways stimulated by paracrine factors released by keratinocytes in response to UVR [11][12][13]. In human melanocytes the balance between Rac and Rho activation is a strong determinant of melanocyte dendrite formation [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%